An Analysis of Geoffrey Leech’s Pragmatic Stylistics in the Lyrics of the Songs “Sialnya, Hidup Harus Tetap Berjalan” and “Untungnya, Hidup Harus Tetap Berjalan” by Bernadya - Sofia Ika Putri; Sukarjo Waluyo (Sabda: Jurnal Kajian Kebudayaan, 2026)
This study aims to describe and analyze the stylistic aspects, including phonology, lexicon, grammar, and semantics, in the lyrics of the songs “Sialnya, Hidup Harus Tetap Berjalan” and “Untungnya, Hidup Harus Tetap Berjalan” by Bernadya, based on Geoffrey Leech's stylistic theory. This study uses descriptive qualitative research with the content analysis method. The research data consists of song lyrics excerpts analyzed based on the linguistic elements contained therein. The results show that in terms of phonology, there is the use of rhyme, rhythm, and sound repetition that supports the emotional atmosphere of both song lyrics. In terms of lexical aspects, the selection of simple and communicative diction is able to convey depth of meaning through its emotional value and context of use. In terms of grammatical aspects, the effective and straightforward sentence structure clarifies the main ideas being conveyed. In addition, in terms of semantic aspects, conceptual and connotative meanings are found that indicate a shift in perspective from disappointment to acceptance of the realities of life. These four stylistic aspects are interrelated and form a complete unity of meaning, so that the lyrics not only function as an expression of feelings, but also as a linguistic work that has aesthetic value and can be studied scientifically.Keywords: stylistics, phonology, lexical, grammatical, semantic, song lyrics.